ALEJANDRO DUQUE AMUSCO, «Noche escrita (Antología poética 1976-2020)», edición y prólogo de José Corredor-Matheos, Sevilla, Renacimiento, 2021, 214 pp. - Balcells Doménech, José María (Lectura y signo, 2023)
Reseña